1993
DOI: 10.1159/000261580
|View full text |Cite
|
Sign up to set email alerts
|

In situ Remineralization of Enamel Lesions using Continuous versus Intermittent Fluoride Application

Abstract: Remineralization of early enamel lesions was studied in situ using a F chewing gum or a F-releasing device (FRD). Enamel specimens with subsurface lesions were mounted in removable lower appliances in 6 adults. A F-free dentifrice was used for all regimens. Test groups chewed five sticks/day (0.1 mg F/stick), or one FRD (0.5 mg F/day) was mounted in the midline of the appliance. The microhardness was measured after the 21-day intraoral exposure, and in vitro acid resistance testing was performed. Separate spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1
4

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
0
8
1
4
Order By: Relevance
“…In this intraoral study, the root lesions con tained roughly twice the fluoride demonstrated in enamel for respective F gum-or FRD-treated specimens, although the locations of the peak concentrations differed. For enam el lesions, the peak concentration was located in the super ficial 5 ,um [Wang et al, 1993], whereas in the root lesions the F peak appeared in or subjacent to the surface layer. Likewise, in both root surface and coronal lesions, the F up take o f FRD-treated lesions exceeded the F gum-treated le sions by approximately twofold.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In this intraoral study, the root lesions con tained roughly twice the fluoride demonstrated in enamel for respective F gum-or FRD-treated specimens, although the locations of the peak concentrations differed. For enam el lesions, the peak concentration was located in the super ficial 5 ,um [Wang et al, 1993], whereas in the root lesions the F peak appeared in or subjacent to the surface layer. Likewise, in both root surface and coronal lesions, the F up take o f FRD-treated lesions exceeded the F gum-treated le sions by approximately twofold.…”
Section: Discussionmentioning
confidence: 90%
“…In this report, the root surface carious lesions studied were derived from an intraoral investigation in which the remineralization of enamel lesions using a F gum or a FRD was described previously [Wang et al, 1993], where the F gum-treated and FRD-treated enamel lesions demonstrated 35.5 and 34.3% remineralization, respectively. Additional ly, the peak F uptake from the FRDs approximated 2,000 ppm F and was generally twofold higher than in those lesions treated with the F gum.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of using intra-oral experimental caries models in the evaluation of the anticaries potential of new products, such as mouthrinse solutions, chewing gums and slow-release devices, is well accepted [Backer-Dirks, 1966;Creanor et al, 1992;Manning and Edgar, 1992;Lamb et al, 1993;Toumba and Curzon, 1993;Wang et al, 1993]. A variety of models have been developed with the aim of establishing effective fluoride (F) regimens for the promotion of remineralisation [Fejerskov et al, 1994;ten Cate, 1994].…”
mentioning
confidence: 99%
“…Örnekler tamponlanm›fl asit solüsyonundan ç›kart›ld›ktan sonra bidistile su ile y›kand› (17,18). Mine bloklar› MTPA akrilik dü¤melerine gömülerek hasta a¤z›na tafl›nd› (fiekil 1).…”
Section: S Su Ub Bj Je Ec Ct Ts S a An Nd D M Me Et Th Ho Od Ds Sunclassified
“…For preparing artificial caries lesions in other words for demineralisation of the specimens, they were immersed in 0.1 mol/L lactic acid-sodium hydroxide buffer (20 mL/specimen) containing 1 per cent sodium carboxymethyl cellulose, 3mmol/L calcium, 1.8 mmol/L phosphate, and 0.263 mmol/L F (pH 4.0) at a constant temperature of 37°C for 39 hours. The specimens were rinsed thoroughly in double-distilled water after being removed from the buffered acid solution (17,18). The enamel blocks were carried into the patients' mouth by embedding in to the acrylic button on MTPA ( Figure 1).…”
Section: S Su Ub Bj Je Ec Ct Ts S a An Nd D M Me Et Th Ho Od Ds Smentioning
confidence: 99%